Ovens, Peter et al (2012) Developing inquiry for learningRoutledge (New York & London) isbn 978‐0‐415‐59877‐4 226 pp £24.99 http://www.routledge.com/books/details/9780415598774. (21st December 2012) - Smyth, Robyn
Summary The authors provide some useful ideas and a bridge from face‐to‐face into blended learning contexts that teachers interested in inquiry pedagogy may find useful. There are various scaffolds and exemplars as well as exploration of appropriate digital tools that can be of use for critical inquiry. If the content of this book is likely to be relevant to you, I advise you may find only parts of it of interest or use. Robyn Smyth